Updated heat capacities of \(^161-164\)Dy nuclei - Le, Huong; Tran, Dong Xuan; Nguyen, Ngoc Anh; Nguyen, Minh Hien; Tran, Cong Duy; Nguyen, Hung (Communications in Physics, 2023)
This work presents the updated heat capacities of \(^161-164\)Dy nuclei in the nuclear temperature region from 0 to 1 MeV. The updated heat capacities are obtained within the canonical ensemble method making use of the most recent and recommended experimental nuclear level density (NLD) data together with those calculated within the back-shifted Fermi gas (BSFG) model with energy-dependent parameters. By comparing the updated heat capacities with the un-updated ones, which are obtained by using the old experimental NLD data and the BSFG with energy-independent parameters, we found that the updated and un-updated heat capacities are almost identical at low temperature, but differ from each others at high temperature. This discrepancy can be interpreted by the damping of nuclear shell structure with increasing the excitation energy. Besides, we observe that the S-shape in the updated heat capacities is much more pronounced in even-even Dy isotopes than in even-odd ones, whereas the un-updated heat capacities do not clearly exhibit this S-shape. Therefore, the updated heat capacities should provide a more convincing evidence for the signature of pairing phase transition in nuclear systems.